2001
DOI: 10.1097/00041327-200106000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Ophthalmic Manifestations of Head Trauma

Abstract: Head trauma causes a number of neuroophthalmic manifestations. The afferent and efferent pathways are vulnerable to traumatic injury, although the efferent system is more commonly affected. Loss of consciousness may not be a reliable predictor of specific neuro-ophthalmic outcomes, but neuroimaging abnormalities may.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 18 publications
6
43
0
1
Order By: Relevance
“…10 The eyes are often involved in head injury (directly and indirectly) with neuroophthalmic deficits. 2,[4][5][6][7][8]11,12 Most ophthalmologists when faced with injured patients tend to focus on obvious ocular manifestations such as contusions and laceration. Subtle manifestations may be equally important and may go unrecognized.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…10 The eyes are often involved in head injury (directly and indirectly) with neuroophthalmic deficits. 2,[4][5][6][7][8]11,12 Most ophthalmologists when faced with injured patients tend to focus on obvious ocular manifestations such as contusions and laceration. Subtle manifestations may be equally important and may go unrecognized.…”
Section: Discussionmentioning
confidence: 99%
“…13 As was found in our study, high velocity impact due to RTA is the commonest cause of head injury reported, 4 with young men most frequently involved. 2 Trauma patients often have multiple injuries including ocular involvement. Several retrospective studies have reported neuro-ophthalmic findings a few months after head trauma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations